Analysis of Mental Health Substance Abuse–Related Emergency Department Visits from 2002 to 2008. Issue 3 (July 2013) - Chakravarthy, Bharath; Tenny, Montessa; Anderson, Craig L.; Rajeev, Sindhya; Istanbouli, Tala; Lotfipour, Shahram
Background: Mental health substance abuse (MHSA)-related visits in the emergency department (ED) are a growing concern. Methods: This study analyzed MHSA ED visits by age, gender, ethnicity, region, season, and duration of stay between 2002 and 2008 using the National Hospital Ambulatory Care Survey (NHAMCS). The authors used descriptive statistics and examined ED length of stay using a generalized linear model with a log link, and compared length of stay for these visits. Results: Mental health–related visits increased from 6.4% of visits in 2002 to 7.0% in 2008 ( P = .002). Substance abuse–related visits increased from 1.8% to 2.1% ( P = .004). Substance abuse-related visits accounted for a 49% increase (CI = 0.051–0.23%) in the total mental health visits to the ED. Male visits increased whereas female visits remained unchanged, with non-Latino white males showing the highest increase. The southern United States had the highest increase in MHSA visits. MHSA visits (5.6 hours) were on average 1.2 hours longer than other non–MHSA-related visits (4.4 hours). MHSA-related visits had a higher percentage of all visits on weekends (2.3%) than on weekdays (2.0%; P < .00005). Conclusions: Concentrated programmatic efforts to decrease the burden of MHSA visits to the ED may reduce the burden of disease.